Principle of territorial integrity: Political consequences of the search for the final status of Kosovo and Metohija - Surlić Stefan; Lazarević Andrijana (Srpska Politička Misao)
The paper analyzes the principle of territorial integrity in the context of the dispute over the final status of Kosovo and Metohija. Without taking a position on the legal disputes, the authors provide an overview of the theoretical debate on territorial integrity and define the political consequences for Serbia's territorial integrity since Kosovo's* unilateral declaration of independence in 2008. Despite the constant mention of integrity as inseparable from sovereignty, the paper highlights the political practice in which Serbia's "territorial integrity" has been turned into an appeal to other states to respect the principle of inviolability of borders. Support for Kosovo's independence by leading Western countries conditioned Serbia to engage in a dialogue with temporary and then permanent administrative institutions in Pristina. The paper concludes that territorial integrity has been reduced to a declarative dimension, as the political demand for the protection of the Serbian community's rights in Kosovo and Metohija has obligated Belgrade to make many concessions, including recognizing the sovereign rights of Pristina's institutions.